2019
DOI: 10.1088/1742-6596/1315/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Students problem-solving abilities using the problem-based learning model with a metacognitive approach

Abstract: This article is about research on the study of improving students’ problem-solving abilities in the learning process using the Problem Based Learning learning model with the Metacognitive approach. This article also contains a study of the interaction between the learning model and the students’ mathematical prior knowledge towards problem-solving abilities, and the study of student behavior in improving mathematical problem-solving skills. The research uses quantitative research methods with research subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The application of this learning model i experimental class has a positive effect on improving problem-solving abi especially for students with low MPK level, as well as those with high to medium le This is because there is more acceptance for students with a lower MPK level in the class than in than the control class. Students with medium and high MPK levels h relatively higher increase in problem-solving abilities because they are also motivat carry out team-assisted activities with others and with students with lower MPK le This was performed to enable lecturers to organize or arrange appropriate lear steps, thereby increasing the students' mathematical solving ability [7,10,12,13,33,40 Based on the previous explanation, it was concluded that the increase in the problemsolving ability of students taught with the team-assisted individualization type of cooperative learning model is better than those lectured with the conventional method for all mathematical prior knowledge levels. Asides from being influenced by the learning model, prior mathematical knowledge contributes to differences in the students' increased mathematical problem-solving ability.…”
Section: Mathematical Problem-solving Ability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The application of this learning model i experimental class has a positive effect on improving problem-solving abi especially for students with low MPK level, as well as those with high to medium le This is because there is more acceptance for students with a lower MPK level in the class than in than the control class. Students with medium and high MPK levels h relatively higher increase in problem-solving abilities because they are also motivat carry out team-assisted activities with others and with students with lower MPK le This was performed to enable lecturers to organize or arrange appropriate lear steps, thereby increasing the students' mathematical solving ability [7,10,12,13,33,40 Based on the previous explanation, it was concluded that the increase in the problemsolving ability of students taught with the team-assisted individualization type of cooperative learning model is better than those lectured with the conventional method for all mathematical prior knowledge levels. Asides from being influenced by the learning model, prior mathematical knowledge contributes to differences in the students' increased mathematical problem-solving ability.…”
Section: Mathematical Problem-solving Ability Analysismentioning
confidence: 99%
“…Students with medium and high MPK levels have a relatively higher increase in problem-solving abilities because they are also motivated to carry out team-assisted activities with others and with students with lower MPK levels. This was performed to enable lecturers to organize or arrange appropriate learning steps, thereby increasing the students' mathematical solving ability [7,10,12,13,33,40].…”
Section: Mathematical Problem-solving Ability Analysismentioning
confidence: 99%